Cheirolepidiaceous diversity: an anatomically preserved pollen cone from the Lower Jurassic of southern Victoria Land, Antarctica - Harper, Carla (My University, 2015)
To date, the vast majority of fossils described for the extinct conifer family, the Cheirolepidiaceae, have been reported from compression/impressions primarily from Cretaceous rocks; there are fewer reports from permineralizations and the Jurassic. New specimens have recently been discovered in siliceous blocks composed of fusainized layers of plant remains that alternate with fine-grained sediments from the Carapace Nunatak (Lower Jurassic) locality of southern Victoria Land, Antarctica. Specimens were prepared using standard serial cellulose-acetate peel technique, transmitted-light microscopy, and SEM analysis. The cones are ellipsoidal, up to 5.5 mm long, and consist of helically arranged microsporophylls, each with a slender stalk containing a single vascular bundle; the distal lamina is peltate and most closely resembles those of the Classostrobus. Four to seven pollen sacs are arranged in an annular cluster abaxial to the sporophyll stalk. In situ Classopollis pollen ranges from 18 to 60 μm in equatorial diameter with an average diameter of 30 μm. In addition to these well-preserved pollen cones there is a large diversity of vegetative conifer remains within the Carapace Nunatak material including leaf and stem fragments. The discovery of the pollen cones in combination with vegetative remains provides additional information on the reproductive biology of the Cheirolepidiaceae and increases the probability of developing a whole-plant concept for this Jurassic permineralized conifer.
PUBLISHED
Keywords: Conifer; Permineralization; Classopollis; Classostrobus; Volcanic environment; Carapace Nunatak; Smart & Sustainable Planet; ANTARCTICA; CONES; Cheirolepidiaceae; Conifer; FOSSIL; Fossil Fungi; Fossil pollen; JURASSIC; PLANT MACROFOSSILS